2020
DOI: 10.1021/acs.accounts.0c00395
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regioselective and Stereospecific Ring-Opening Cross-Coupling of Aziridines: Experimental and Computational Studies

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Aziridines, i.e., the smallest saturated N-heterocycles, serve as useful building blocks in synthetic organic chemistry. Because of the release of the large ring strain energy accommodated in the small ring, (ca. 27 kcal/mol), aziridines undergo ring-opening reactions with a variety of nucleophiles. Therefore, among the synthetic reactions utilizing aziridines, regioselective ring-opening substitutions of aziridines with nucleophiles, such as heteroatomic nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…Aziridine is a three-membered azaheterocycle, which is a versatile building block in organic synthesis, especially as a precursor for the ring opening reaction of N-containing natural products. 94 Transition metal complexes have been used as reactive catalysts for C-N bond cleavage in an S N 2 fashion to form azametallabutanes. [94][95][96] The regio-selective ring opening C-B cross-coupling reaction of 2-arylaziridines via a Pd(P(t-Bu) 2 Me/bpy) catalyst was shown to give β-amino-alkylboronates.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aziridine is a three-membered azaheterocycle, which is a versatile building block in organic synthesis, especially as a precursor for the ring opening reaction of N-containing natural products. 94 Transition metal complexes have been used as reactive catalysts for C-N bond cleavage in an S N 2 fashion to form azametallabutanes. [94][95][96] The regio-selective ring opening C-B cross-coupling reaction of 2-arylaziridines via a Pd(P(t-Bu) 2 Me/bpy) catalyst was shown to give β-amino-alkylboronates.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
“…94 Transition metal complexes have been used as reactive catalysts for C-N bond cleavage in an S N 2 fashion to form azametallabutanes. [94][95][96] The regio-selective ring opening C-B cross-coupling reaction of 2-arylaziridines via a Pd(P(t-Bu) 2 Me/bpy) catalyst was shown to give β-amino-alkylboronates. This reaction is useful in natural product synthesis and amino-functionalization.…”
Section: Reaction Selectivity Studies Using Hybrid Methodsmentioning
confidence: 99%
“…In particular, ring‐opening reactions of small saturated heterocycles [1] and bridged heterocycles [2,3] have been extensively investigated, mainly because their huge ring strain can significantly derive ring‐opening to proceed. The most successful small heterocycles employed in ring‐opening reactions have been the epoxides [1a,b,c,d,4] and aziridines, [1a,h,i,5] which can be subjected to the attack from a series of nucleophilic reagents to furnish aliphatic alcohols and amines respectively. Nevertheless, C‐heteroatom bond cleavage in five‐ or six‐membered rings is usually a rather challenging task due to their negligible ring strain [6]…”
Section: Figurementioning
confidence: 99%
“…The ring opening of aziridines with carbon nucleophiles constitutes an important class of synthetic method to access biologically relevant β‐functionalized amines. Even if an isolated example of arylative cross‐coupling of a terminal sulfonyl‐protected aziridine has been reported with a copper catalyst, [43] more interesting results have been obtained using palladium catalysis [50] . In particular, Takeda and Minakata found that catalyst [SIPr−Pd(cinnamyl)Cl] has a pivotal role in a C‐2‐selective and enantiospecific arylative ring opening of 2‐arylaziridines occurring in very mild reaction conditions (Scheme 13, eq.…”
Section: Boronic Acids and Derivativesmentioning
confidence: 99%